The DNA Methylome of the Hyperthermoacidophilic Crenarchaeon Sulfolobus acidocaldarius - Couturier, Mohea; Lindås, Ann-Christin (Frontiers in Microbiology, 2018)
DNA methylation is the most common epigenetic modification observed in the genomic DNA of prokaryotes and eukaryotes. Methylated nucleobases, N6-methyl-adenine (m6A), N4-methyl-cytosine (m4C) and 5-methyl-cytosine (m5C), detected on genomic DNA represent the discrimination mark between self and non-self DNA when they are part of restriction-modification systems in prokaryotes (Bacteria and Archaea). In addition, m5C in Eukaryotes and m6A in Bacteria play an important role in the regulation of key cellular processes. Although archaeal genomes present modified bases as in the two other domains of life, the significance of DNA methylations as regulatory mechanisms remains largely uncharacterized in Archaea. Here, we began by investigating the DNA methylome of Sulfolobus acidocaldarius. The strategy behind this initial study entailed the use of combined digestion assays, dot blots and genome resequencing, which utilizes specific restriction enzymes, antibodies specifically raised against m6A and m5C and single-molecule real-time (SMRT) sequencing, respectively, to identify DNA methylations occurring in exponentially growing cells. The previously identified restriction-modification system, specific of S. acidocaldarius, was confirmed by digestion assay and SMRT sequencing while, the presence of m6A was revealed by dot blot and identified on the characteristic Dam motif by SMRT sequencing. No m5C was detected by dot blot under the conditions tested. Furthermore, by comparing the distribution of both detected methylations along the genome and, by analyzing DNA methylation profiles in synchronized cells, we investigated in which cellular pathways, in particular the cell cycle, this m6A methylation could be a key player. The analysis of sequencing data rejected a role for m6A methylation in another defense system and also raised new questions about a potential involvement of this modification in the regulation of other biological functions in S. acidocaldarius.